Physician-Modified Fenestrated Endografts for Managing the Ruptured or Symptomatic Aortic Aneurysm: Technique Overview and Clinical Outcomes. (November 2018) - Singh, Aminder; Mafeld, Sebastian; Williams, Robin; McCaslin, James
Purpose: Fenestrated endovascular aneurysm repair (FEVAR) grafts have a 10- to 12-week manufacturing time and are generally not available for emergency cases of symptomatic or ruptured aortic aneurysm. In the absence of other alternatives, conventional off-the-shelf stent grafts can be modified by trained operators to treat these complex cases. The aim of this study is to present a single-center experience of physician-modified FEVAR. Methods: A retrospective review was performed of all physician-modified FEVAR identified from the hospital endovascular database at a single tertiary referral center between September 1996 and September 2017. Results: Eight cases of urgent or emergency endovascular aneurysm repair (EVAR) with physician-modified grafts were identified. Mean follow-up was 44 weeks (range: 5-106 weeks). Outcomes for all implanted grafts (7/8 cases) included 100% technical success, 14% rate of endoleak, no procedure-related complications, no adverse visceral events, 0% 30-day mortality and 100% 1-year target vessel patency, and freedom from aneurysm-related death. There was a 14% (1/7 cases) per patient reintervention rate. Conclusion: Modifying EVAR grafts is a highly technical process requiring meticulous planning and extensive elective experience with FEVAR. The current series demonstrates that physician modification of endografts for urgent or emergency abdominal aortic aneurysm repair is feasible and a safe alternative to open surgical aneurysm repair.